2020
DOI: 10.1021/acs.jpca.0c02807
|View full text |Cite
|
Sign up to set email alerts
|

NMR Spin–Spin Coupling Constants Derived from Relativistic Four-Component DFT Theory—Analysis and Visualization

Abstract: An unambiguous assignment of coupling pathways plays an important role in the description and rationalization of NMR indirect spin–spin coupling constants (SSCCs). Unfortunately, the SSCC analysis and visualization tools currently available to quantum chemists are restricted to nonrelativistic theory. Here, we present the theoretical foundation for novel relativistic SSCC visualization techniques based on analysis of the SSCC densities and the first-order current densities induced by the nuclear magnetic dipol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 48 publications
(88 reference statements)
0
16
0
Order By: Relevance
“…Therefore, that basis scheme has been chosen for all their calculations. Moreover, considering a failure of Nakanishi et al in prediction of the Se–Se distance in 50c, [ 341 ] Komorovsky et al [ 388 ] were very meticulous about the geometry optimization methodology. They calculated equilibrium geometries at the quasi‐relativistic ZORA/QZ4P level using PBE0 and BP86 functionals as well as at the corresponding nonrelativistic levels, and obtained a noticeably shorter Se–Se distances at the relativistic levels of DFT theory.…”
Section: The Qc Computations Of Selenium Nmr Spectrummentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, that basis scheme has been chosen for all their calculations. Moreover, considering a failure of Nakanishi et al in prediction of the Se–Se distance in 50c, [ 341 ] Komorovsky et al [ 388 ] were very meticulous about the geometry optimization methodology. They calculated equilibrium geometries at the quasi‐relativistic ZORA/QZ4P level using PBE0 and BP86 functionals as well as at the corresponding nonrelativistic levels, and obtained a noticeably shorter Se–Se distances at the relativistic levels of DFT theory.…”
Section: The Qc Computations Of Selenium Nmr Spectrummentioning
confidence: 99%
“…Overall, the geometric parameters obtained at the relativistic DFT level occurred much closer to the experimental values than that obtained at the nonrelativistic DFT level. Another important issue of Komorovsky et al, [ 388 ] that has not been considered by Nakanishi and Hayashi, [ 341 ] is the potential energy surface. Komorovsky et al have found two main conformers resulting in a huge difference in corresponding Se–Se SSCCs, while Nakanishi and Hayashi considered only one structure.…”
Section: The Qc Computations Of Selenium Nmr Spectrummentioning
confidence: 99%
See 3 more Smart Citations